2018
DOI: 10.1016/j.ajhg.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cancer-Predisposition Gene Testing in an Adult Multiple Primary Tumor Series Shows a Broad Range of Deleterious Variants and Atypical Tumor Phenotypes

Abstract: Multiple primary tumors (MPTs) affect a substantial proportion of cancer survivors and can result from various causes, including inherited predisposition. Currently, germline genetic testing of MPT-affected individuals for variants in cancer-predisposition genes (CPGs) is mostly targeted by tumor type. We ascertained pre-assessed MPT individuals (with at least two primary tumors by age 60 years or at least three by 70 years) from genetics centers and performed whole-genome sequencing (WGS) on 460 individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 52 publications
4
52
1
2
Order By: Relevance
“…Genetic tests are available for many CPS, but have been traditionally performed on just one or few genes selected according to clinical suspicion. Recently, the application of next‐generation sequencing (NGS) has improved the diagnostic rate . The main aim of this study is to validate an integrated workflow for the genetic diagnosis of pediatric cancer patients by proposing as first tier either a candidate gene analysis or a genomic test (whole exome sequencing or array‐CGH) depending on phenotype and family history.…”
Section: Introductionsupporting
confidence: 86%
“…Genetic tests are available for many CPS, but have been traditionally performed on just one or few genes selected according to clinical suspicion. Recently, the application of next‐generation sequencing (NGS) has improved the diagnostic rate . The main aim of this study is to validate an integrated workflow for the genetic diagnosis of pediatric cancer patients by proposing as first tier either a candidate gene analysis or a genomic test (whole exome sequencing or array‐CGH) depending on phenotype and family history.…”
Section: Introductionsupporting
confidence: 86%
“…A recent study identified this variant in three individuals with multiple primary tumors, so the presumption of pathogenicity is stronger. However, none of whom had typical hereditary leiomyoma or renal cell carcinoma tumors (Whitworth et al, 2018). Although it is a well-established pathogenic variant for autosomal recessive FH deficiency, its association with renal cell carcinoma is less well defined.…”
mentioning
confidence: 98%
“…Two patients reported a history of uterine fibroids but not cutaneous leiomyomas. Uterine fibroids are the most common benign tumors in women worldwide (Merrill, 2008;Zimmermann, Bernuit, Gerlinger, Schaefers, & Geppert, 2012), and in isolation are not indicative of HLRCC by themselves (Menko et al, 2014;Pithukpakorn & Toro 1993-2018-2018 which is predicted to affect the protein function using in silico prediction tools, hence the role of the c.1431_1433dupAAA, in this case, remains unclear (Chen et al, 2014).…”
mentioning
confidence: 99%
“…The second non‐chromosome 3 translocation t(10;17)(q11.22;p12) underwent sequencing as part of the NIHR BioResource Rare Diseases project (see methods) and was analyzed previously as part of a multiple primary tumor cohort with a history of facial fibrofolliculomas, recurrent pneumothoraces, and RRC. At that time, no abnormality was detected but subsequently reanalysis identified candidate translocation breakpoints that were supported by two overlapping Manta calls for the chromosome 10 and chromosome 17 breakpoints at chr17:17218211‐17 218 214 (17p11.2) and chr10:43236047‐43 236 050 ( 10q11.21) that were supported by 22 spanning and 10 split reads and a secondary call at chr17:17218216‐17 218 217 and chr10:43236058‐43 236 059 by 15 spanning and 18 split reads (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Genome‐wide variant calling was jointly performed on all samples using GATK unified genotyper (version 3.7‐0‐gcfedb67) . DNA from one proband underwent GS as part of the NIHR BioResource Rare Diseases study with sequencing and primary bioinformatics performed as previously described . Data were aligned to genome build GRCh37 and all analyses were performed identically with appropriate adjustments for differences in genome build.…”
Section: Methodsmentioning
confidence: 99%